Penilaian Tekstur Tulang Bandeng Presto dengan Instrumen Instron dan Secara Organoleptik - Jamaluddin Jamaluddin; Budi Rahardjo; Suwedo Hadiwiyoto (agriTECH, 1999)
The use of Instron instrument to predict bone texture of fish have been conducted by studying the relationship of data from Instron with organoleptic scoring by the panelists. Samples were fishbone and bone from pressure cooked fish respectively. Temperature distribution during cooking was measured using Data Logger, the results showed that the time for heating up to cooking temperature were generally very short, 10-15 minutes, for any temperature range of cooking, while time for cooling down to room temperature were long, 40-60 minutes. There were significant relationship between data obtained from measurement of the bone fragility expressed in force using Instron instrument and organoleptic scoring given by panelists. Nonlinear relationships were found for all samples between organoleptic scores and objective analysis using Instron except for the range temperature of cooking between 110°C and 125°C below the force of 100 N for the sample of bone, showed by the regression of Y -20,29X + 136,90 with Y is forces and X is organoleptic scores.